Pewność sytuacji jednostki w demokratycznym państwie prawnym - Tabernacka, Magdalena (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The standard of legal security that an individual is provided within a state appears to essentially turn on the certainty of his or her legal status. Therefore, where the public governance bodies operate in the reality ruled by the principle of the separation of the three powers it is their responsibility not to extend the range of the power vested in each of them individually or promote an instrumentalisation of law. One of the axiological foundations of the democratic state of law is that of the state respecting its citizens, which results in the actual use of consultation instruments, participatory instruments and consensual instruments – inclusive of mediation, in the making and enforcing of the laws. In addition to the basic characteristics shared by the model of the democratic state of law and the model founded on the correct standard of legal security (the certainty of one’s status) enjoyed by an individual within the state, the latter comprises a range of other elements: material and formal guarantees of social and economic pluralism; legal guarantees of the stability of the citizens’ legal status in the economic context; and normative and factual instruments which enable to keep the executive sphere and the judiciary apart from political influences.
Keywords: participation; democracy state of law; authority; reliability of a legally established order